Willingness-to-pay against dementia: Effects of altruism between patients and their spouse caregivers - Markus König; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2004)
Objectives: Preferences of both Alzheimer patients and their spouse caregivers are related to a willingness-to-pay (WTP) measure which is used to test for the presence of mutual (rather than the conventional one-way) altruism. Methods: Identical contingent valuation interviews were conducted in 2000 - 2002 for 126 Alzheimer patients and their caregiving spouses living in the Zurich metropolitan area (Switzerland). We elicit WTP three hypothetical treatments of the demented patient. The treatment Stabilization prevents the worsening of the disease, bringing dementia to a standstill. Cure restores patient health to its original level. In No burden, dementia takes its normal course while caregiver's burden is reduced to its level before the disease. Results: Different characteristics of therapies are reflected in differences in WTP values. Accepting WTP values as expression of preferences, one finds that patients do not rank Cure higher than No burden; implying that their WTP is entirely altruistic. Caregiving spouses rank Cure before Burden, some 40 percent of their WTP reflecting an altruistic motive again. Discussion: The evidence suggests that WTP values are reliable measures of subjective preferences even in Alzheimer patients. Using this indicator, it is found that only caregivers have extra WTP for Cure, implying that curing dementia has value exclusively to them.
Keywords: 330; Willingness to pay; Krankheit; Gesundheitskosten; Schweiz